A dual shape pore model to analyze the gas adsorption data of hierarchical micro-mesoporous carbons. (30th June 2021) - Jagiello, J.; Chojnacka, A.; Pourhosseini, S.E.M.; Wang, Z.; Beguin, F.
Abstract: Hierarchical micro/mesoporous carbons obtained by template carbonization were investigated by nitrogen adsorption/desorption and gave a type IV isotherm with a H1 hysteresis loop closing perfectly near P/P0 = 0.6. When using the 2D-NLDFT theory to calculate the pore size distribution (PSD) from the adsorption branch of the isotherms, while assuming slit pores with a heterogeneous rough surface (2D–HS–SLIT model), an unexpected artifact was observed ca. 3.5 nm. Recognizing that the H1 hysteresis loop is usually related to the adsorption in materials with cylindrical pores, where in general it is recommended to use the desorption branch for the pore size analysis, we have applied the 2D–HS–SLIT model to the adsorption isotherm up to P/P0 = 0.2 and a cylindrical pore model to the desorption isotherm down to P/P0 = 0.2. Interestingly, the application of this dual shape pore model to hierarchical micro/mesoporous carbons of various mesopore sizes and oxygenated surface functionalities shows an excellent fit with the experimental isotherms, while the mesopore peak in the PSDs is narrower, and the previously labeled artifact is eliminated. It is noteworthy that the cumulative surface area values are significantly larger than when applying the 2D–HS–SLIT model, what is due to the larger surface area of cylindrical than slit-shaped mesopores. Graphical abstract: Image 1